Preparation and Characterization of Integrated Bulk of Silica Aerogels - Zhang, Weina; Hao, Libo; Lu, Jilong; Zhu, Jianwei (Asian Journal of Chemistry, 2012)
The integrated bulk of silica aerogels were synthesized by two step sol-gel process using tetraethoxysilane as precursor followed by supercritical drying technique. The X-ray diffraction, nitrogen adsorption-desorption method, differential thermal -thermogravimetric analysis, infrared spectroscopy and scanning electron microscopy analysis were used to observe the structure, the surface morphology and the chemical composites of the prepared silica aerogels. The results showed that the prepared silica aerogels had continual netted, amorphous and mesoporous microstructure with even spherical nanometer particles and porous channel. The density, averaged pore size and specific surface area of the prepared silica aerogels with high thermal stability were 0.12 g cm-3, 14.9 nm and 925.7 m2 g-1, respectively.